MANAJEMEN MADRASAH BERBASIS NILAI PESANTREN DI MTS ALHIDAYAH MUARA TELANG - Irwan Fathurrochman; Febriana Sholeha; Rahma Dhania; Yuli Ferbi Yanti (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2022)
Modernization with various impacts should be anticipated the educator by mastering two competences, science and technology competency and spiritual competency. A weakness in one of those competences makes the students’ development is not balanced which finally lead to their split personality. Therefore, the human potential includes both of competences must be internalized and developed in students simultaneously. In that context, this research conducted to discuss the implementation of school management based on the pesantren value which is developed at MTs Alhidayah Muara Telang. The approach of this research is qualitative on case study. The results of this research conclude that: Pesantren value developed at MTs Alhidayah Muara Telang is the essential value defined in Five Spirits of Madrasah, (2) The Teachers’ Management at MTs Alhidayah Muara Telang includes: Planning, Recruitment, Selection, Training, Teachers Development, Evaluation of Work Performance, and Compensation, (3) The curriculum management at MTs Alhidayah covered: the subject planning, curriculum organizing, curriculum implementation, and evaluation of Madrasah programs.